Peran Teknologi Informasi Pada Masa Pandemi Terhadap Kegiatan Belajar Di Sekolah - Jusuf Wahyudi; Khairil Khairil; Ila Yati Beti; Yupianti Yupianti; Devina Ninosari (Universitas Dehasen Bengkulu, 2022)
Information and communication technology is progressing faster and faster, and human activities can complete tasks more quickly and efficiently. Information technology makes it easier for people to communicate, interact and act in various ways. The technology that can use to meet face-to-face needs in large quantities is Zoom Cloud Meeting, Google Meet, and Cisco Webex, and there are several other applications for similar purposes but are less desirable. During a pandemic such as Covid 19 and its various derivatives, since it was known until now, it is a scary thing for the community because the impact arising from contracting this virus can result in death. So from 2020 until early 2022, school learning activities were closed due to the PSBB policy from the government. It will be very detrimental to society, especially for school-age children who still need guidance from teachers in understanding lessons. So we need another policy in its implementation, namely the implementation of online or online learning. The utilization of information technology such as Zoom, Google Meet or Cisco Webex as a face-to-face tool between teachers and students through internet media is essential. This situation also does not escape the State 3 Seluma Senior High School, which also carries out online teaching and learning activities.